Energy Expenditure and Oxygen Consumption During Activities of Daily Living in People With Multiple Sclerosis and Healthy Subjects: An Ecological Approach to Estimate Real-Life Fatigue and Fatigability - Manca, Andrea; Ventura, Lucia; Martinez, Gianluca; Cano, Antonella; Matta, Gabriele; Aiello, Elena; Deriu, Franca (Archives of physical medicine and rehabilitation, 2021)
To compare oxygen consumption and energy expenditure (EE) of the activities of daily living (ADL) in people with multiple sclerosis (PwMS) and healthy subjects. Cross-sectional observational study. Outpatient care facilities. Twenty-four moderately impaired PwMS and 21 healthy controls (N=45). Not applicable. Oxygen consumption, EE rate, and total EE assessed by portable open-circuit spirometry during the accomplishment of a comprehensive set of 14 ADL. Body composition was also assessed with bioelectrical impedance analysis. Body cell mass was used to normalize metabolic rates between groups. PwMS exhibited significantly higher oxygen consumption than controls in transfer and mobility tasks (walking with stairs: +10.4%, P=.04; without stairs: +15.2%, P=.002; driving: +10.4%, P=.04) and higher EE rates for walking (+13.6%, P=.01). ADL completion took significantly longer in PwMS. Consequently, when total EE to complete each ADL was considered, PwMS used significantly more energy in 10 of the 14 ADL. Of these, “climb stairs” and walking with or without stairs showed the largest differences (+100%, +99.5%, +79.3%, respectively; all P values<.0005), followed by “dressing” (+48.8%; P=.002), “laundry” (+41.7%; P=.007), and “shopping” (+40.1%; P=.003). Moderately disabled PwMS display oxygen consumption and EE rates during ADL that are comparable to those of matched healthy subjects, except for the activities that involve walking. Although metabolic rates were not different for the majority of ADL, PwMS showed higher total EE to complete the same activities at a comparable work intensity, which may contribute to the burden of “real-life” tiredness and fatigue typically described in this population. Importantly, the subjective Modified Fatigue Impact Scale score significantly correlated to EE and oxygen consumption of selected ADL, such as “make a bed,” “driving,” “clean surfaces,” and “climb stairs.” The joint employment of open-circuit spirometry during ADL and body composition analysis allows an accurate metabolic characterization of PwMS, who frequently complain of fatigue.